THE RELATIONSHIP BETWEEN FOREIGN INVESTMENT AND MACROECONOMIC INDICATORS: EVIDENCE FROM TURKEY - Guluzar Kurt Gumus (European Scientific Journal, ESJ, 2015)
Foreign investment flows, comprised of direct and portfolio investments, generally indicate an upward trend in developing countries. During 1980s, developing countries have eased the restrictions on foreign investment, since it is the major source of external finance for those countries. Although there is a controversy on the effects of foreign investment, most of the studies indicate that foreign investment generates positive effects on host countries. Turkey is one of the leading emerging economies, which receives considerable amount of foreign investment flows. Turkish policy makers make substantial efforts to attract foreign investment. Those efforts include streamlining investmens, transferring funds to home countries, and offering special tax incentives to foreign investors. Studies on this issue generally focus on the determinants of foreign investment. Another point is that most of the studies analyze only one type of foreign investment, either direct or portfolio. Contrary to the existing literature, this study deals with both types of investments. The study aims at analyzing the relationship between foreign investment and major economic and financial indicators in Turkish economy. Namely, those indicators are current account deficit, real exchange rate, nominal interest rate and stock exchange index. To examine these relationships, the period of 2003-2013 has been surveyed by using Granger causality analysis. The results signify that bi-directional relationship exists between the foreign direct investment and the rates of real exchange and interest. On the other hand, the foreign portfolio investment has bi-directional relationship with Borsa Istanbul Index. Further, Borsa Istanbul Index is the Granger cause of the foreign direct investment, while the rates of real exchange and interest are Granger causes of the foreign portfolio investment. Finally, the current account deficit is the Granger cause of both types of the foreign investments.